1964
DOI: 10.4141/cjas64-026
|View full text |Cite
|
Sign up to set email alerts
|

The Birth and Weaning Weights of Highland and Hereford Cattle and Their Reciprocal Crosses

Abstract: Birth and weanins data were "$t:"mH t9i7 tot960 on 219

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
4
0

Year Published

1966
1966
1992
1992

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
4
4
0
Order By: Relevance
“…Male calves averaged 3.4lb heavier at birth than heifer calves in the current study. This agrees with reports of other workers (Lawson and Peters 1964).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Male calves averaged 3.4lb heavier at birth than heifer calves in the current study. This agrees with reports of other workers (Lawson and Peters 1964).…”
Section: Discussionsupporting
confidence: 94%
“…Birth weight increased as the age of dam increased and did not appear to decline with the older animals. This agrees with Lawson and Peters (1964), although Dawson, Phillips, and Black (1947) found that birth weight did not increase after the age of the dams reached six years. Male calves averaged 3.4lb heavier at birth than heifer calves in the current study.…”
Section: Discussionsupporting
confidence: 76%
“…The Hereford, Highland, and reciprocal cross Highland x Hereford and Hereford x Highland heifer calves that were weaned in [1957][1958][1959][1960] (Lawson and Peters 1964) (Lawson 1975(Lawson , 1981 than calves out of each of the other groups.…”
Section: Experimental Herdmentioning
confidence: 99%
“…Bison in l9l6 Highlands in 1956 (Lawson and Peters 1964) were incorporated (Lawson and Peters 1964;Lawson 197 5, 1976 (Lawson 1975) (Lawson 1976 (Lawson 1976 …”
mentioning
confidence: 99%